Effect of Compensation, and Training on Work Discipline and its impact on Employee Performance of the Regional Research and Development Planning Agency in Dharmasraya Regency - ., Desmil Putra; Heryanto, (Archives of Business Research, 2019)
This study tries to test the Effect of Compensation, and Training on Work Discipline and its impact on the Employee Performance of the Regional Research and Development Planning Agency in Dharmasraya Regency. This study uses descriptive quantitative methods. The study population consisted of 22 people from employees. To obtain a valid and realistic instrument, the validity and reliability test, normality test, multicollinearity test and heterocedasticity test were tested. The data analysis technique used is linear regression analysis, t test, f test, determination coefficient, and path analysis using the SPSS program, with α = 0.05. The results of the study showed that Compensation and Training were able to improve the Discipline of employees of BAPPEDA in Dharmasraya Regency. Then Compensation, Training and Discipline were able to improve the performance of employees of BAPPPEDA in Dharmasraya Regency. In addition, Discipline is able to increase the influence of Compensation and Training on the performance of employees of BAPPPEDA in Dharmasraya Regency. The empirical findings indicate that to improve the performance of employees of BAPPPEDA in Dharmasraya District, it is necessary to pay attention and focus more on improving Compensation, Training and Work Discipline.